Optimasi Algoritma AES Dengan Implementasi Parallel Dalam Pengamanan Data Digital - Nur Wulan; Siti Sundari; Rapna Dewi (Unit Pengelola Jurnal Universitas Harapan Medan, 2022)
Digital data security is the protection of private data to prevent unwanted access to computer databases or websites. In this study, cryptographic techniques are used which is a way to enter data. Why data needs to bedigital, it can prevent potential loss, reduce data risk, and reduce crime. In this study, we will optimize the AESalgorithm, the AES algorithm has a linear speed, where the greater the number of N blocks to be executed, thehigher the execution time. The design in this study uses a unified modeling language and mysql as a database. Thepurpose of this study is to implement the parallel AES algorithm for the encryption and decryption process ofdigital data and analyze and provide recommendations for the algorithm that will be used in the future byconsidering the comparison results obtained.